Robotic-Assisted XRF Testing System for In-Situ Areal Density Measurement of Light-Sensitive Explosive Coatings - Chang Xu; Haibin Xu; Ke Wu; Bo Chen; Pengju Dong; Yaguang Sui; Hai Chen (Sensors, 2025)
The light-sensitive explosive (silver acetylide–silver nitrate, SASN) sprayed on structural surfaces can be synchronously initiated by intense pulsed flash, thereby simulating cold X-ray blow-off events characterized by thermal–mechanical coupling effects. By adjusting the areal density of SASN coatings, proportional blow-off impulse levels can be achieved. To address the challenge of in situ and non-destructive areal density measurement for SASN coatings, this study developed an X-ray fluorescence (XRF) detection system integrated with a six-axis spray robot. Excitation parameters (50 kV, 20 μA) and geometric configuration (6 cm focal distance) were optimized to establish a quadratic calibration model between Ag Kα counts and areal density (0–80 mg/cm2) with high correlation (R2 = 0.9987). Validation experiments were conducted on a uniformly coated SASN plate (20 × 20 cm) to evaluate the consistency between XRF and sampling methods. The XRF-measured areal density averaged 12.722 mg/cm2 with a coefficient of variation (CV) of 3.19%. The reference value obtained by the sampling method was 12.718 mg/cm2 (CV = 1.57%). The relative deviation between the two methods was only 0.03%, confirming the feasibility of XRF for the quantification of SASN coatings. The XRF system completed measurements in 1 h, achieving a 77.8% time reduction compared to conventional sampling (4.5 h), significantly enhancing efficiency. This work provides a reliable solution for in situ and non-destructive quality control of energetic material coatings.